Efficacy of bronchoscopic thermal vapor ablation in patients with heterogeneous emphysema and lobar quantification by three-dimensional ventilation/perfusion single-photon emission computed tomography/computed tomography: a prospective pilot study from China - Zhu, Wenjun; Zhang, Yuchen; Herth, Felix; Liu, Dan; Zhu, Hui; Shi, Jingyu; Zhang, Chujie; Tang, Gongshun; Luo, Fengming (Chinese medical journal, 2022)
Chronic obstructive pulmonary disease (COPD) is characterized by emphysema and airflow limitation and is one of the leading causes of morbidity and mortality worldwide. Endoscopic lung volume reduction (ELVR) is a minimally invasive technique for patients with severe hyperinflation and advanced emphysema. To date, the most investigated form of ELVR is valve implantation, which is to place valves in all the segments of an emphysematous lobe. However, valve replacements do not achieve adequate lung volume reduction in the presence of interlobar collateral ventilation (CV).[1] In addition, with the heterogeneity existing within the treatment lobe, complete lobar treatment from implants may result in excessive reduction of the less diseased segments. Thus, a more targeted approach of the most severe emphysematous parts of the lobe is warranted.